Kohlberg's moral judgment among Jesuit senior high school students in Indonesia an exploratory study - Sugiarto, Johannes Berchmans 1938-
This study looked into the profile of stages of moral reasoning of the three year level students in three Senior High Schools run by Jesuits in Central Java, Indonesia. The study was conducted to answer the following questions:(1) Can moral reasoning of the Indonesian students in the Jesuit senior high schools, be categorized into stages according to Kohlberg's theory? (2) Will the moral statements given by the older students to the presented moral dilemmas cluster in higher stages of moral development? (3) Are there signs of moral development among the three levels of students of senior high schools? and lastly, (4) Do the patterns of moral reasoning of the Indonesian students support Kohlber's theory?
Thesis (M.Ed.)--University of the Philippine, Diliman.
Typescript.
Vita.
Keywords: Moral education (Secondary) -- Indonesia; Judgment (Ethics).